Difference in the relative intensities Raman of the perovskite PLT with temperature - Joya, M R; Fonseca, K M; Barba-Ortega, J (AIP conference proceedings, 2014)
La-modified PbTiO3 -based ceramics (PLT) are the subject of many studies. The experimental measurement and the theoretical calculation of Raman scattering intensities present a number of challenges. In the treatment of experimental data, anharmonic force fields permit the calculation of combination and overtone intensities as well as the resolution of anharmonic resonances. Vibrational intensities provide information about the molecular charge distribution and its change during a vibration. On most cases Raman scattering is sensitive to the degree of crystallinity in a sample. Typically a crystalline material yields a spectrum with very sharp, intense Raman peaks, whilst an amorphous material will show broader less intense Raman peaks. Intensity reproducibility is not a trivial matter. Furthermore, properties of the sample such as optical transparency and homogeneity can affect observed intensity, even when the overall sample composition is fixed. A corrected spectrum showing relative peak areas (and therefore relative cross-sections) may be sufficient for sample identification. In this paper we make a comparison of the Raman intensities relative to the PLT compound for different temperatures.